Distance mapping of the foot and ankle joints using weightbearing CT: The cavovarus configuration. Issue 4 (June 2021) - Lintz, François; Jepsen, Maui; De Cesar Netto, Cesar; Bernasconi, Alessio; Ruiz, Maria; Siegler, Sorin
Highlights: In this case-control study, three-dimensional models were produced from weight-bearing CT images and distance maps for multiple joints were generated. Significant differences in surface-to-surface interaction at the foot and ankle joints between cavovarus and normally-aligned feet were idenfied. Ankles in cavovarus feet exhibited increased distances in the posterior quadrants of the talar dome and in the posterior aspect of the medial gutter. At the subtalar joint, cavovarus feet demonstrated decreased articular distances at the anterior/middle facet and increased distance at the medio-posterior aspects of the posterior facet. At the sinus tarsi, the lateral aspect of the talonavicular joint, the naviculocuneiform and the tarsometatarsal joints there was a significant increase in surface-to-surface distance in cavovarus patients. This technology can provide an accurate and visual information regarding intra-articular deformities. Abstract: Introduction: The goal of this study was to characterize the abnormal joint surface interaction at the ankle, hindfoot and midfoot joints of the cavovarus foot using distance mapping on weightbearing computed tomography (WBCT) images by comparing a series of cavovarus feet to a series of normally-aligned feet. Methods: In this case-control study, ten feet (10 patients) with asymptomatic cavovarus shape (cases; N = 10) were compared to 10 matched-paired (by age, gender and body mass index) normally-aligned feet (10 patients) (controls; N = 10). Three-dimensional models were produced from the images and distance maps representing joint surface configuration were generated for the ankle, hindfoot and midfoot joints. The distance maps for each joint were then compared between the two groups and between regions in the same group. Results: In the cavovarus group there was a significant increase in surface-to-surface distance at the posterior tibiotalar joint and a reduced distance at the anterior part, together with a greater distance at the posterior half of the medial gutter. Also, a decrease in surface-to-surface distance on the anterior half of the anterior facet and an increased distance on the posterior quadrants of the posterior facet of the subtalar joint were found. At the sinus tarsi, the lateral aspect of the talonavicular joint, the naviculocuneiform and the tarsometatarsal joints there was a statistically significant increase in surface-to-surface distance in cavovarus patients as compared to controls. Conclusion: Distance mapping analysis on WBCT images identified significant differences in surface-to-surface interaction at the foot and ankle joints between cavovarus and normally-aligned feet. Level of evidence: Level III, case-control study.